2010
DOI: 10.1175/2010waf2222359.1
|View full text |Cite
|
Sign up to set email alerts
|

A Local Formulation of the Ensemble Transform (ET) Analysis Perturbation Scheme

Abstract: Following ideas from the local ensemble transform Kalman filter, a local formulation of the ensemble transform (ET) analysis perturbation scheme is developed by partitioning the numerical weather prediction model domain into latitude bands or latitude-longitude blocks. In comparison with analysis perturbations from the original ''global'' ET formulation, analysis perturbations from the ''banded'' or ''block'' ET formulations are much more consistent with estimates of analysis error variance. Banded or block ET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…Initial conditions for the NOGAPS forecast ensemble are generated using a nine-banded local ensemble transform (ET) scheme (McLay et al 2010). In this methodology, short-term ensemble forecasts are linearly combined, under the constraint of an estimate of the analysis error variance, to produce a set of perturbations to the analysis from the Naval Research Laboratory Atmospheric Variational Data Assimilation System-Accelerated Representer (NAVDAS-AR) (Rosmond and Xu 2006;Chua et al 2009).…”
Section: Nogapsmentioning
confidence: 99%
“…Initial conditions for the NOGAPS forecast ensemble are generated using a nine-banded local ensemble transform (ET) scheme (McLay et al 2010). In this methodology, short-term ensemble forecasts are linearly combined, under the constraint of an estimate of the analysis error variance, to produce a set of perturbations to the analysis from the Naval Research Laboratory Atmospheric Variational Data Assimilation System-Accelerated Representer (NAVDAS-AR) (Rosmond and Xu 2006;Chua et al 2009).…”
Section: Nogapsmentioning
confidence: 99%
“…Given these promising results, the present study investigates the incorporation of a variant of the Takaya et al [2010b] diurnal SST scheme into the NWP component of the U.S. Navy's global EPS. In addition, this study investigates the adaptation of the local ensemble transform (ET) ensemble generation scheme of McLay et al [2010] to generate SST analysis perturbations. Hence, the EPS design for the present study is distinct from those of Takaya et al [2010a] and Tennant and Beare [2011]in that it takes account of both SST diurnal variation and SST initial‐state uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…In its purest form, only one set of transformation coefficients is used for the entire state. However, McLay et al (2010) have shown that smoothly blending the transformation coefficients relevant to large regions such as the tropics and extra-tropics can lead to performance advantages. In this first study, we approximate Eq.…”
Section: Description Of the Ensemble Transform Techniquementioning
confidence: 99%
“…Each member now creates unique atmospheric lateral BC from 28 members of the global NOGAPS ensemble (step 3). The members of the global ensemble are produced using perturbation methodology based on the banded ET as described in McLay et al (2008McLay et al ( , 2010. The banded ET produces initial perturbations by transforming 6-h ensemble forecast perturbations to be consistent with analysis error estimates.…”
Section: Implementation Of the Mesoscale Ensemble Systemmentioning
confidence: 99%